Numeracy in Authentic Contexts Making Meaning Across the Curriculum (Springer Singapore, 2018)
This book is based on the notion that there are many ways in which mathematics learning can be achieved for students and that not all of them are focused on the mathematics classroom. It explores the foundational numeracy principles of the non-mathematical subject areas and aligns these to the Australian numeracy-learning continuum. It demonstrates, in detail, the extent to which numeracy competencies underpin successful learning in all the subject areas of the curricula. It validates a focus of developing numeracy competencies through learning in the arts, science and other discipline areas with which school students to engage with in order develop holistically, but which are not subjected to national assessment practices. It is developed around the notion of 'praxis', putting theory into practice in order to respond to the urgent need for students to be supported in their efforts to increase their numeracy capabilities in a world where extensive amounts of new information are often presented in graphical or data based formats. Additionally, it offers perspectives on developing all students' capacities to become numerate in school contexts and presents inclusive, differentiated lesson examples as an alternative way of exploring numeracy in the context of teaching and learning in real-world classroom contexts.